Romania - Implementation of Regional Development and Integration with Other EU Operational Programs : Issues and Options for Maximizing Absorption and Impact of EU Funds - McLean, Keith; Sen, Aditi (2012)
This policy note summarizes the results of technical assistance offered in support of the Government of Romania (GOR) in its implementation of regional development programming for European Union (EU) accession. Three important questions confront Romania's policy makers: (i) how to operationalize regional and local development, given the context of EU structural funds; (ii) how to develop effective mechanisms for multi-level planning and resource allocation to filter resources (EU net transfers) to the regional and local levels where they will be most useful; and (iii) how to build on the successful experiences of the EU-15 and of projects supported by the World Bank and other donors that use bottom-up planning and implementation processes to develop effective local projects. This note looks at some answers to these questions as well as at the issues surrounding possible integration of the Regional Operations Programme (ROP) with other relevant EU operational programs, notably environment and rural development. Finally, this report aims to help inform the World Bank on how best to design future regional and rural development support programs, given the new context of EU funding.